Acupuncture for painful diabetic peripheral neuropathy: a systematic review and meta-analysis - Luolin Zhou; Tong Wu; Zhishan Zhong; Lichen Yi; Yuemei Li (Frontiers in Neurology, 2023)
BackgroundPainful Diabetic Peripheral Neuropathy (PDPN) is a common complication of diabetes, it severely affects the quality of life of patients. Acupuncture has been shown to be effective in the treatment of PDPN. To evaluate the efficacy and safety of acupuncture for pain relief in patients diagnosed with diabetic peripheral neuropathy, we conducted a systematic review and meta-analysis.MethodWe thoroughly searched specific databases, which included PUBMED, EMBASE, Web of Science, the Cochrane Library, the Chinese Biomedical Literature Database, the Chinese National Knowledge Infrastructure, China Science and Technology Journal Database and the Wanfang Data. All randomized controlled trials of acupuncture therapy for PDPN with pain change scales were included. Included studies were assessed for methodological quality according to the risk of bias from the Cochrane handbook. Meta-analyses were carried out to analyze the outcomes, subgroup analyses, sensitivity analyses, and funnel plot analyses were undertaken.ResultsThis systematic review evaluated a total of 25 trials of acupuncture therapy in combination with conventional treatment, involving a total of 1,561 patients with PDPN. According to the results, among 16 trials using VAS scores with a total of 1,552 patients, 2 acupoint injection trials (MD −2.38, 95% CI: −2.76 to −2.01, p < 0.00001), 12 acupuncture trials (MD −1. 31, 95% CI: −1.60 to −1.02, p < 0.00001) and 2 moxibustion trials showed that acupuncture therapy combined with conventional treatment improved pain better than conventional treatment (MD −2.50, 95% CI: −2.76 to −2.24, p < 0.00001). In the subgroup analysis of the acupuncture group, the results of the 5 trials in which the location of acupuncture was only in the limbs (MD −1.27, 95% CI: −1.54 to −1.01, p < 0.00001) and the 7 trials both in limbs and torso (MD −1.38, 95% CI: −1.81 to −0.95, p < 0.00001) also demonstrated that acupuncture was effective in pain improvement.ConclusionThis meta-analysis analyzed the possible efficacy of acupuncture in combination with conventional treatment for pain in diabetic peripheral neuropathy, particularly when acupoints are located in the limbs. However, there are limitations to this meta-analysis and future clinical studies are needed to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023449447, identifier (CRD42023449447).